DIAGNÓSTICO DE FALHA NO SISTEMA PREDIAL DE ÁGUAS PLUVIAIS DE UM PRÉDIO HISTÓRICO ATRAVÉS DO USO DE TERMOGRAFIA DE INFRAVERMELHO - Zanini, Camila Mokwa; Socoloski, Rafaela Falcão; Dias, Raquel Buttow Nunes; Zucchetti, Lais; Masuero, Angela Borges (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The heritage buildings have historical and cultural value within the context where they are inserted, and because they have been built with specific techniques and materials, according to their time, should be analyzed with due care. Allied to this, these buildings usually present several pathological manifestations from different factors. In this context, this work aimed to diagnose the origin of infiltration moisture in the external vertical sealing system of a historic building. The method used for this evaluation involved the following steps: anamnesis, rain test, thermography and results analysis. In the anamnesis, it was identified that the infiltration occurred on rainy days and the higher the rainfall intensity, the greater the water intake through the SVVE. The tests were performed after several days without rain, ie the walls had no areas of moisture. The tests were carried out considering the watertightness of the pipes of the rainwater system and the gutters. Infrared thermography was used as a tool for performance evaluation. The results demonstrated that the failure occurred in the fence of the gutters and the used technique allowed the identification of the origin of the pathological manifestation without destructive interventions that compromised the historic building.